Simultaneous multislice diffusion-weighted imaging with short tau inversion recovery fat suppression in bone-metastasizing breast cancer. Issue 130 (September 2020) - Buus, Thomas Winther; Sivesgaard, Kim; Jensen, Anders Bonde; Pedersen, Erik Morre
Highlights: Multiband DWI reduces scan time of whole-body DWI in bone-metastatic breast cancer. Multiband DWI provides image quality similar to conventional DWI. ADC values from multiband DWI are slightly lower than conventional DWI. Abstract: Purpose: To compare image quality and ADC values of simultaneous multislice diffusion-weighted imaging (mb-DWI) with that of conventional DWI (c-DWI) using short tau inversion recovery fat saturation (STIR) in women with bone-metastasizing breast cancer. Method: c-DWI and mb-DWI were acquired at 1.5 T in 23 breast cancer patients from skull base to mid thighs. mb-DWI was compared to c-DWI in terms of subjective image quality, artefacts and bone metastasis lesion conspicuity assessed on a 5-point Likert scale. ADC values of different organs as well as bone metastasis ADC values were compared between c-DWI and mb-DWI. Results: mb-DWI reduced scan time by 48 % compared with c-DWI (1 min 58 s vs. 3 min 45 s per station). mb-DWI provided similar subjective image quality (3.8 vs. 3.7, p = 0.70), number of artefacts (50 vs. 56), severity of these (4.6 vs. 4.7, p = 0.11), and lesion conspicuity (4.2 vs. 4.4, p = 0.31) compared to c-DWI. mb-DWI showed lower mean ADC values in liver (0.5 × 10 −3 mm 2 /s vs. 0.7 × 10 −3 mm 2 /s, p = 0.002) and erector spine muscle (1.3 × 10 −3 mm 2 /s vs. 1.5 × 10 −3 mm 2 /s, p < 0.001). Bone metastasis ADC values from mb-DWI were 6.4 % lower than c-DWI (95 % confidence interval: 5.4%–7.4%, p < 0.001). Conclusions: mb-DWI provides similar subjective image quality to c-DWI with the same level of artefacts. Although bone metastasis ADC values were lower, mb-DWI can substantially reduce scan times of whole-body DWI in women with bone-metastasizing breast cancer.